ACTUALIZING DISTRIBUTIVE JUSTICE IN DIACONAL MINISTRY THROUGH A DIGITAL THEOLOGY APPROACH USING FUZZY MADM (SAW MODEL) - Theo Pilus Candra (Journal Informatic, Education and Management (JIEM), 2026)
Diaconal ministry is a mandate for the church to manifest God's love to the vulnerable. However, in practice, aid distribution is often hindered by assessor subjectivity (elders/deacons), nepotism, and data inaccuracy, leading to the kind of injustice seen in the early church (Acts 6:1). This study proposes an interdisciplinary "Digital Theology" approach by implementing the Fuzzy Multi-Attribute Decision Making (Fuzzy MADM) algorithm as a tool for a Decision Support System (DSS). Unlike rigid binary logic, Fuzzy logic is capable of accommodating the uncertainty of the congregation's economic conditions, which are often vague or ambiguous. By utilizing the SAW (Simple Additive Weighting) method, this study simulates a priority ranking of aid recipients based on measurable pastoral criteria. The results demonstrate that integrating technology into ecclesiastical management can minimize human bias, enhance transparency, and ensure more precise distributive justice in accordance with biblical principles.